Sports facilities create jobs? the economic impact of the presence of sports facilities - Didik Subhakti Prawira Raharja; Nurlan Kusmaedi; Amung Ma’Mun; Berliana Berliana (JUARA : Jurnal Olahraga, 2021)
The presence of sports facilities is supposed to provide space for the community to carry out physical activities and sports competition events, any other impacts involved need to be studied further in order to complete studies in the construction of sports facilities. The purpose of this study is to see the benefits resulting from the presence of sports facilities from an economic perspective. A qualitative approach with a case study design was chosen in this study. Semi-structured interviews, and observations were used in data collection with participants involving policy makers, facility managers and visitors. The results of this study revealed that the presence of sports facilities economic impact by creating jobs both permanent and temporary so that the economy can increase incomes and reduce unemployment and poverty.